iFringe : a fringe analysis application for mobile smart devices - Qian, Kemao (2018)
This paper introduces iFringe, a mobile application that attempts to incorporate the resource heavy fringe analysis algorithms into the smart mobile devices platform. This first step taken towards mobility in the optical processing field aims to become a catalyst for modernization of various aspects of the field as well as to diversify developments to other applications. Predominantly, the motivation of this work stems from the vastly indifferent human interactive method of mobile devices, which enable images displayed on its touch screen to be manipulated in ways that could enhance the fringe analysis experience. Furthermore, given its hardware compatibility to the conventional fringe projection system, these mobile devices could potentially serve as a much more compact replacement. However, one imperative weakness that mobile devices pose is its limited computing ability. Therefore, to examine the feasibility of incorporating the fringe analysis algorithms into a mobile platform, we have implemented two fundamental fringe analysis techniques, namely the Fourier transform fringe analysis method and the phase-shifting technique. Formulas and processing procedures such as discrete Fourier transform (DFT) and quality-guided phase unwrapping, were included in accordance to their original algorithms to test their performance and usability on a smart mobile device. Details of the implementation and the performance results will also be presented in this paper to demonstrate the practicality of these algorithms on the smart mobile device platform.